As assimetrias de gênero nas representações de extraconjugalidades na telenovela Avenida Brasil - Albano, Thaís Cristina (2014)
This dissertation investigates the television representations of gender in relation to the cases of married female and male characters who committed adultery in the Brazilian soap opera Avenida Brasil. To this end, we are referring to a feminist perspective using theoretical scholar‟s ideas that debating the concept of gender, such as Joan Scott and Teresa de Lauretis, and analyze the process of construction and dissemination of social representations from the conceptions of Serge Moscovici. Apart from the theoretical research, our methodological approach consisted of content analysis, based on Laurence Bardin, a technique used in the examination of some selected characters to reinterpret the messages they transmit and reveal the meanings and symbologies that are behind the manifest content. We also conducted field research through the application of questionnaires to two groups of respondents who containing, equally, passersby and college students, both of the two genders, so that we could capture the public\'s perception about the representations of those characters. Thus, it was found that the television media has giving visibility to women presenting them in diverse roles, but without touching the issue of gender differences, as well corroborating with the reproduction of inequalities settled in sex differences, adopting different weights and measures regarding sexuality freely exercised, since that disapproves women, but legitimizes and even praises the men who experience the same situation. Such representations reflect the dictates of an androcentric society, and its impact could be clearly understood by the survey, since much of the respondents, both female viewers as male, showed agreement with the concepts conveyed by the soap opera analyzed.